1981
DOI: 10.2172/5719826
|View full text |Cite
|
Sign up to set email alerts
|

Microcavity hydrogen storage. Final progress report

Abstract: In the microcavity storage system, high pressure hydrogen i s stored in hollow, glass microspheres, 5-15@m. This report presents the results o f an experimental study t o evaluate the performance of commercially available microspheres f o r this application. Eight grades were evaluated and t h e i r characteristics are presented. A substantial f r a c t i o n of the microsphere beds survived the conditions o f storing hydrogen at pressures of 400 atm. establishing t h a t the concept of high pressure hydrogen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…It has the advantages of non-toxic, self-lubrication, good dispersion and fluidity, high pressure resistance, low thermal conductivity, heat preservation, fire resistance, etc. As early as 1977, Teitel [80] proposed the use of micron-sized HGMs as a high-pressure hydrogen storage vessel and made a series of studies on it. The results showed that the hydrogen storage mass density of a HGM could reach the target value calibrated by the U.S. DOE vehicle hydrogen storage vessel in that year, and it was a very promising high-pressure hydrogen storage vessel.…”
Section: Hollow Glass Microspheres (Hgm)mentioning
confidence: 99%
“…It has the advantages of non-toxic, self-lubrication, good dispersion and fluidity, high pressure resistance, low thermal conductivity, heat preservation, fire resistance, etc. As early as 1977, Teitel [80] proposed the use of micron-sized HGMs as a high-pressure hydrogen storage vessel and made a series of studies on it. The results showed that the hydrogen storage mass density of a HGM could reach the target value calibrated by the U.S. DOE vehicle hydrogen storage vessel in that year, and it was a very promising high-pressure hydrogen storage vessel.…”
Section: Hollow Glass Microspheres (Hgm)mentioning
confidence: 99%
“…A significant amount of research on the use of glass microspheres for hydrogen storage has been completed by Robert J. Teitel Associates (RJTA) under contract by the US. Department of Energy through Brookhaven National Laboratory [13][14][15][16]. In 1979 RJTA evaluated several commercial grades of glass microsphere, including Fillite 200/7 and 30017 and 3M D32/4500.…”
Section: Glass Microsphere Sto Rape -mentioning
confidence: 99%
“…Storage and transportation of hydrogen in hollow glass microspheres (HGMS) has been proposed [1][2][3], but has been traditionally hindered by the slow release rates of hydrogen from the spheres.…”
Section: Introductionmentioning
confidence: 99%